EFEKTIVITAS PENERAPAN METODE PQRST TERHADAP HASIL BELAJAR MEMBACA PEMAHAMAN SISWA SDN KEDOYA SELATAN 04 PAGI - Lufi Nabila; Ratnawati Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low reading comprehension learning outcomes in Indonesian among sixth-grade students at SDN Kedoya Selatan 04 Pagi, particularly for explanatory texts. Conventional learning makes it difficult for students to understand complex text structures and leads to less active engagement. Therefore, this study aims to determine the effect of the PQRST (Preview, Question, Read, Summarize, Test) method on students' reading comprehension learning outcomes.This study used a quantitative approach with a one-group pretest-posttest quasi-experimental design. The sample consisted of 30 sixth-grade B students selected using a purposive sampling technique. Data collection was conducted using a multiple-choice test to measure learning outcomes (pretest-posttest).The results showed a significant improvement. The average student score jumped from 43.10 in the pretest to 80.60 in the posttest. The coefficient of determination test showed that the application of the PQRST method contributed 79.6% to the reading comprehension learning outcome. Furthermore, the hypothesis test obtained a value of 0.001 < 0.05, confirming that H1 was accepted.Thus, it can be concluded that there is a significant difference in sixth-grade students' Indonesian reading comprehension learning outcomes after implementing the PQRST method.